'Synthesis, antiinflammatory and analgesic activities of some 1,2,4-thiadiazolidines and 1-4-aryl guanidines' - Naik P.R.; Pandeya S.N. (My University, 2025)
A series of 2,4-dimethyl-3,5-diarylimino-1,2,4-thiadiazolidines (1a-1) and 1-[2-(substituted benzothiazolyl]-1,3-dimethyl-4-aryl guanidines (2a-1) were evaluated for their anti-inflammatory and analgesic activities. Substitution of p-methoxy group (1c and 2c) in the aryl ring resulted in most active compounds in the series in both the activities and were also statistically equipotent than the standard drugs.